2019
DOI: 10.1016/j.diagmicrobio.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem heteroresistance in clinical isolates of OXA-48–producing Klebsiella pneumoniae

Abstract: OXA-48-producing Klebsiella pneumoniae isolates often show growth of colonies within inhibition zones in carbapenem diffusion assays. The nature of these colonies was investigated in a series of clinical isolates of OXA-48producing K. pneumoniae obtained in the context of a hospital outbreak, and they were found to be persistent colonies that reproduced again the same phenotype when they were collected and tested in diffusion assays again. The frequency of mutations conferring resistance to meropenem (8 μg/mL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The ceftolozane-tazobactam resistance mechanisms in ESBL-producing isolates are not well understood. Outer membrane sequence alterations that could play a role in resistance to ceftolozane-tazobactam were not observed among resistant K. pneumoniae, E. coli, and E. cloacae isolates compared to those in genetically similar isolates susceptible to this combination; however, decreased expression of OMP-encoding genes or posttranslational modifications that could play a role in resistance to ␤-lactams (22)(23)(24) were not evaluated and present a limitation of this study. Additionally, efflux extrusion of the antimicrobial or the inhibitor and overexpression of ␤-lactamases could also be important in resistance to ceftolozane-tazobactam.…”
Section: Discussionmentioning
confidence: 88%
“…The ceftolozane-tazobactam resistance mechanisms in ESBL-producing isolates are not well understood. Outer membrane sequence alterations that could play a role in resistance to ceftolozane-tazobactam were not observed among resistant K. pneumoniae, E. coli, and E. cloacae isolates compared to those in genetically similar isolates susceptible to this combination; however, decreased expression of OMP-encoding genes or posttranslational modifications that could play a role in resistance to ␤-lactams (22)(23)(24) were not evaluated and present a limitation of this study. Additionally, efflux extrusion of the antimicrobial or the inhibitor and overexpression of ␤-lactamases could also be important in resistance to ceftolozane-tazobactam.…”
Section: Discussionmentioning
confidence: 88%
“…coli , rates of carbapenem-heteroresistance of 25-32%, detected by disk-diffusion, have been described (24, 25). Furthermore, for OXA-48, presence of colonies within the inhibition zones in disk or gradient diffusion assays for meropenem, independently of the MIC values measured by microdilution, has been reported in Klebsiella pneumoniae producing this carbapenemase (26). Previous studies have shown that the outcomes of in vitro susceptibility testing of tigecycline can be affected by the testing method used, mainly in Acinetobacter baumannii but also for carbapenemase-producing enterobacterales (27).…”
Section: Discussionmentioning
confidence: 99%
“…When third-generation cephalosporins were introduced into clinical use, this difference explains why K. pneumoniae isolates were initially more sensitive to these antibiotics than E. coli strains [ 78 ]. Porin deficiency reduces the uptake of β-lactams and, in combination with ESBLs activity, may confer clinical resistance [ 40 , 62 , 79 ]. The emergence of imipenem-resistant subpopulations with decreased levels of OmpK36 was reported by Adams-Sapper et al ( Table 1 ).…”
Section: Prevalence and Mechanisms Of Heteroresistance In K Pneumoniaementioning
confidence: 99%